The institutional and economic limits to bargaining decentralization in Italy - Francesco D'Amuri; Cristina Giorgiantonio (Institute for the Study of Labor (IZA), 2015)
Italy is not immune from the long term process towards greater bargaining decentralization under way in Western Europe. The article surveys the main actions, either defined by social partners or by government intervention, which have attempted to encourage this process in recent years, without altering the relative importance of different levels of bargaining. Empirical evidence shows that firm-level bargaining has been associated with innovative managerial practices, but also that a significant share of firms would be willing to sign contracts that would grant higher wages or preserve occupational levels in order to obtain higher flexibility in the use of the workforce. From an institutional standpoint, the main obstacles preventing the adoption of such deals are: i) unresolved issues related to the measurement of trade unions' weight at the national level and to the coexistence of two different workers' representation systems, ii) limits to contract enforcement, iii) limited scope for action of second level bargaining in determining both wages and work organization. The effectiveness of tax breaks encouraging a closer link between wage and productivity at the firm level has been undermined by poor monitoring and frequent changes to the eligibility criteria.
Keywords: J31; J41; J51; J53; 330; industrial relations; labour law; salary structure